Leptomeningeal carcinomatosis can be presenting manifestation of breast carcinoma - Mandic Stojmenović, Gorana; Pavlović, Aleksandra M; Skender Gazibara, Miilica; Grujičić, Danica; Radojičić, Aleksandra; Čovičković Šternić, Nadežda (Vojnosanitetski pregled, 2016)
Introduction. Leptomeningeal carcinomatosis (LC) is a serious complication occuring in solid cancer patients with rather poor prognosis. Case report. We presented a 47-year-old woman with the 6-month history of diffuse headache, nausea and visual obscuration. Initially, clinical status and brain magnetic resonance imaging (MRI) indicated syndrome of idiopathic intracranial hypertension. Due to clinical progression and high papillary stasis, cerebrospinal fluid (CSF) examination was performed only after ventriculoperitoneal shunt was implanted. This led to a significant although transient clinical improvement. Futher investigations led to the diagnosis of invasive lobular breast carcinoma and repeated CSF analysis revealed malignant breast carcinoma cells. In this case LC was an initial presentation of a malignant disease. Conclusion. In the presence of a high clinical suspicion of LC, in spite of initially negative findings, a clinician should persist in repeating relevant tests, such are MRI with larger amounts of gadolinium and high-volume cytological CSF analyses in order to make the diagnosis.
Keywords: breast neoplasms; neoplasm metastasis; meningeal neoplasms; diagnosis; differential